A Surprising Cause of Contained Aortic Rupture: Perforation from a Lumbar Osteophyte - Kontopodis, Nikolaos; Ioannou, Christos V. (AORTA, 2020)
We describe a patient with contained aortic rupture due to perforation from a protruding lumbar osteophyte, who was treated by open surgery. This case underlines that less common aortic pathologies are possible, which require a high suspicion index to be diagnosed.
Keywords: contained aortic rupture; pseudoaneurysm; osteophyte